Perencanaan Pemeliharaan Mesin Chin Fong 110 Ton Menggunakan Metode RCM dan FMEA untuk Mengurangi Produk Cacat - Yusuf Mauluddin; Encep Jianul Hayat; Dadang Permana (Jurnal Kalibrasi, 2026)
This study aims to plan a maintenance system for the Chin Fong 110 Ton machine in the piercing stamping process at PT. XYZ in order to reduce the level of defective products caused by machine damage and lack of planned maintenance. The method used is Reliability Centered Maintenance (RCM) which uses Failure Mode and Effect Analysis (FMEA) to identify critical components and determine maintenance action priorities. The research process includes collecting historical machine failure data, calculating the Risk Priority Number (RPN) value, and determining the type of maintenance actions such as Condition Directed (CD) and Time Directed (TD). The results show that the main cause of machine malfunctions is the lack of planned maintenance. Based on the RCM analysis, the pinion drive shaft, wet clutch, and slide (ram) components are recommended to use CD measures, while the flywheel and main gear use TD measures. The implementation of this maintenance plan is projected to improve machine reliability and reduce the defect rate while extending the machine's service life and increasing production process efficiency. The contribution of this research is to provide a reliability-based maintenance planning model that can be used as a reference for manufacturing companies in optimizing machine performance and maintaining product quality in a sustainable manner.